Fire, volcanism and climate change: the main factors controlling mercury (Hg) accumulation rates in Tropical Lake Lantoa, Sulawesi, Indonesia (∼16,500–540 cal yr BP) - Nalbant, Jalene; Schneider, Larissa; Hamilton, Rebecca; Connor, Simon; Biester, Harald; Stuart-Williams, Hilary; Bergal-Kuvikas, Olga; Jacobsen, Geraldine; Stevenson, Janelle (Frontiers in Environmental Chemistry, 2023)
The effects of climate change on mercury (Hg) cycling are still not well understood as climate changes are usually gradual and can only be assessed using high-resolution archives.Our study site (a small, lowland tectonic lake in Sulawesi, Indonesia) provides a unique opportunity to further understanding of Hg cycling in the Southeast Asian (SEA) tropics during the transition from the Pleistocene to the Holocene, a period of significant climate variability.We present a high-resolution record of Late Glacial and Holocene Hg deposition within the sediments of tropical Lake Lantoa, Sulawesi. Using a multi-proxy framework (including pollen, charcoal, carbon:nitrogen ratio and high-resolution geochemistry records) we investigate the response of HgARs in sediments to shifts in climate between ~16,488 and 538 cal BP. This period encompasses the Bølling-Allerød (BA) warming, Younger Dryas (YD) cooling and Holocene warming events, providing new insights into the effects of global climatic transitions on Hg accumulation rates (HgAR) in SEA sediments. The Pleistocene Termination had the highest HgAR and substantial variability (µ= 11.32, 5.38 -33.91 µg m -2 yr -1 ), when drier conditions and high charcoal accumulation rate suggest that fire activity was the main source of Hg to the lake. The Holocene Transition is marked by a decrease in HgAR (µ= 8, 3.50 -18.84 µg m -2 yr -1 ) as humid conditions preclude forest burning, followed by high HgAR (µ= 11.35, 3.30 -158.32 µg m -2 yr -1 ) in the Early Holocene. Mercury accumulation rate in the Late Holocene (µ= 3.80, 1,67 -43.65 µg m -2 yr -1 ) was the lowest in the Lake Lantoa record, marked by the lowest fire events and a stable catchment. Increase in carbon:nitrogen ratio during the Late Holocene, coupled with decrease in HgAR suggest that the establishment of lowland forest resulted in a decrease in Hg erosion/leaching to the lake . Our results demonstrate that forest fires, vegetation change and volcanism are important drivers of Hg to Lake Lantoa, a relationship which is strongly mediated by climate and lake-catchment dynamics.